Socio-Cultural factors affecting women economic empowerment in Pakistan: a situation analysis - Choudhry, Abubakar Nazeer; Abdul Mutalib, Rozita; Ismail, Nur Syakiran Akmal (2019)
Women empowerment is a global key concern in terms of development. It has various shapes over the time and space but closely connected to the economic, socio-cultural, familial or interpersonal, legal, political, and psychological domains. Pakistan like many other countries have signatory of several international declarations till now to empower the women, but at the same time Pakistani women experience high level of discriminations and economic dependency is one of them. A variety of academic literature is available regarding women economic empowerment around the globe and in Pakistan. This article aims to describe a descriptive review of socio-cultural factors affecting women economic empowerment in Pakistan. The major socio-cultural factors are educational barriers, decent work and access to property. All these socio-cultural factors are potential barriers and create hurdles for women to become empowered. Further the state has failed to promulgate the policies in true letter and spirit. It seems that documenting a women empowerment policy has a state concern but has failed to bring out the oppressed and marginalized group out of oppression